Endothelial ACKR1 is induced by neutrophil contact and down-regulated by secretion in extracellular vesicles - Guo, Xinying; Khosraviani, Negar; Raju, Sneha; Singh, Joshya; Farahani, Nikki Zamani; Abramian, Madlene; Torres, Victor J.; Howe, Kathryn L.; Fish, Jason E.; Kapus, Andras; Lee, Warren L. (Frontiers in Immunology, 2023)
Atypical chemokine receptor-1 (ACKR1), previously known as the Duffy antigen receptor for chemokines, is a widely conserved cell surface protein that is expressed on erythrocytes and the endothelium of post-capillary venules. In addition to being the receptor for the parasite causing malaria, ACKR1 has been postulated to regulate innate immunity by displaying and trafficking chemokines. Intriguingly, a common mutation in its promoter leads to loss of the erythrocyte protein but leaves endothelial expression unaffected. Study of endothelial ACKR1 has been limited by the rapid down-regulation of both transcript and protein when endothelial cells are extracted and cultured from tissue. Thus, to date the study of endothelial ACKR1 has been limited to heterologous over-expression models or the use of transgenic mice. Here we report that exposure to whole blood induces ACKR1 mRNA and protein expression in cultured primary human lung microvascular endothelial cells. We found that contact with neutrophils is required for this effect. We show that NF-kB regulates ACKR1 expression and that upon removal of blood, the protein is rapidly secreted by extracellular vesicles. Finally, we confirm that endogenous ACKR1 does not signal upon stimulation with IL-8 or CXCL1. Our observations define a simple method for inducing endogenous endothelial ACKR1 protein that will facilitate further functional studies.